Probing the acyl carrier protein–Enzyme interactions within terminal alkyne biosynthetic machinery. Issue 12 (12th September 2018) - Su, Michael; Zhu, Xuejun; Zhang, Wenjun
Abstract : The alkyne functionality has attracted much interest due to its diverse chemical and biological applications. We recently elucidated an acyl carrier protein (ACP)‐dependent alkyne biosynthetic pathway, however, little is known about ACP interactions with the alkyne biosynthetic enzymes, an acyl‐ACP ligase (JamA) and a membrane‐bound bifunctional desaturase/acetylenase (JamB). Here, we showed that JamB has a more stringent interaction with ACP than JamA. In addition, site‐directed mutagenesis of a non‐cognate ACP significantly improved its compatibility with JamB, suggesting a possible electrostatic interaction at the ACP‐JamB interface. Finally, error‐prone PCR and screening of a second non‐cognate ACP identified hot spots on the ACP that are important for interacting with JamB and yielded mutants which were better recognized by JamB. Our data thus not only provide insights into the ACP interactions in alkyne biosynthesis, but it also potentially aids in future combinatorial biosynthesis of alkyne‐tagged metabolites for chemical and biological applications. © 2018 American Institute of Chemical Engineers AIChE J, 64: 4255–4262, 2018